Improving Student Learning Outcomes in Fiqh Learning through the Student Problem Based Learning Model at MI Nurul Jihad - Muzanni; Najla (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to improve the learning motivation of fifth grade students of MI Nurul Jihad in the subject of Fiqh through the application of the Problem Based Learning learning model. The background of the study identified that the learning process tends to focus on memorization, does not involve students actively, and results in low learning motivation. This condition is influenced by limited facilities and infrastructure, lack of mastery of science and technology by teachers, and low student interest in learning. Based on these problems, this classroom action research was formulated to answer the question: "Can the use of the Problem Based Learning learning model improve students' learning motivation in the field of Fiqh studies of fifth grade MI Nurul Jihad?" This study uses the Classroom Action Research method that focuses on the implementation of the Problem Based Learning model. Data were collected through tests, observations, and documentation, then analyzed descriptively qualitatively. The results of initial observations showed low student participation and learning outcomes, where only 66.7% of students (10 out of 15) achieved completion with an average score of 65.33. After implementing cycle I of the PBL model, there was a significant increase in student learning outcomes, with 80.0% of students (12 out of 15) achieving completion and the class average score increasing to 75.0.